TANGGUNG JAWAB HUKUM INSTITUSI PENDIDIKAN DALAM PENANGANAN PERUNDUNGAN DI SEKOLAH: STUDI IMPLEMENTASI REGULASI DI SMP KABUPATEN KEDIRI - Iswahyudi, Eko (Yayasan Nusantara Hasana Berdikari, 2025)
This study examines the implementation of anti-bullying regulations in junior high schools in Kediri Regency and the obstacles faced in their implementation. The results of the study indicate that schools have implemented various policies, such as anti-bullying regulations, character education programs, and counseling services for students. The role of teachers, students, and parents greatly determines the effectiveness of these policies, although parental involvement is still a challenge. In terms of legal responsibility, schools strive to carry out their obligations in accordance with Law Number 35 of 2014 concerning Child Protection and Permendikbud Number 82 of 2015, but there are still variations in effectiveness in handling bullying cases, depending on the availability of resources and the understanding of educators regarding the regulations. Some of the main obstacles faced in implementing regulations include teachers' lack of understanding of the mechanisms for handling bullying, limited facilities, and minimal awareness of students and parents. To overcome these obstacles, recommended optimization strategies include increasing teacher capacity through regular training, strengthening reporting mechanisms, and increasing the role of parents in preventing bullying. In addition, support from local governments is needed to provide counseling service facilities and campaign for anti-bullying programs. With a comprehensive strategy, it is hoped that schools can create a safer and bullying-free environment.